Gluing of quasisymmetric imbeddings in the problem of quasiconformal extension - Aseev, V.V.; Sychev, A.V.; Tetenov, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We prove a general theorem on gluing of quasisymmetric imbeddings. Using this theorem, we solve the problem of quasiconformal extension from a one-parameter family of quasiconformal triangles of a special type that do not have a general estimate of quasiconformal convexity.